(untitled) (Journal of Forensic Medicine & Toxicology, 2016)
Road traffic accidents are the major causes of death worldwide. Road traffic accident is the third major preventable cause of death. Head injury is the single most common cause of mortality in road traffic accidents; head being the most vulnerable part of the body. The present prospective study was conducted in Department of Forensic Medicine, P.D.U. Medical College and associated Hospital, Rajkot from 01-01-2008 to 31-12- 2008. The objective of this study was to analyze the pattern of fatal head injury among road traffic accidents. During that period out of 2159 autopsies, 298 cases of road traffic accidents were selected for present study which accounts 13.8% deaths. Our study shows 99 (33.22%) victims were male of middle age group (21-30years), male: female ratio was 10.5:1. 101(33.89%) victims were pedestrians, followed by occupants of heavy four wheelers, two wheelers and three wheelers. Head injury in 161(54.03%) followed by heamorrhagic shock in 51(17.11%) were the main causes of death.